İfa uğruna edim - Balcı, Betül (My University, 2024)
İfa Uğruna Edim başlıklı bu doktora tezinde borçlunun ifayı borçlanılan edimden farklı bir edimle gerçekleştirme teşebbüsü ve bunun hukuki sonuçları incelenmiştir. Borçlunun ifaya yönelik bu girişimi tarafların amaçlarına göre farklı şekillerde ortaya çıkmakta olup, hukuki so-nuçları ve tarafların hak ve borçları bu nitelendirmeye göre şekillenmektedir. Hukukumuzda kural borçlanılan edime uygun ifa olup, borçlu ancak borç ilişkisinde kararlaştırılan edimi ifa ederek borcundan kurtulmakta, alacaklı da yalnızca bu edimin ifasını talep edebilmektedir. An-cak ifa ikameleri olarak adlandırılan ve bu kuralın istisnasını oluşturulan hukuki imkânlarla bor-cun borç ilişkisinde kararlaştırılan edimden farklı bir edimle ifası mümkün hale gelmiştir. Çalış-ma konumuzu oluşturan ifa uğruna edim, bu istisnai durumlardan birisini oluşturmakta, alacak-lıya alacağını elde edebilmesi için ilave bir olanak tanımakta, borçluya ise borcunu borçlanılan edimden farklı bir edimle yerine getirme imkanı sağlanarak ifanın gerçekleşmesi için zaman ka-zandırmaktadır. İfa uğruna edim Türk ve İsviçre Hukukunda bir kanun hükmüyle genel olarak düzenlenmemiş, Alman Hukukunda ise ifa yerine edimi düzenleyen BGB § 364 hükmünün ikinci fıkrasında bir yorum kuralı olarak benimsenmiştir. Bununla beraber ifa uğruna edim, mevcut bir borcun ifasının bir alacak devri yoluyla gerçekleşmesini düzenleyen TBK m. 192 hükmünde, havale edenin havale alıcısına temel ilişkideki borcunun ifası amacıyla yaptığı hava-lenin ifa uğruna olduğunu yasal bir karine olarak kabul eden TBK m. 556 hükmünde yer bul-muştur. Kanunlarda genel olarak düzenleme alanı bulunmayan ancak özellikle ticaret hayatında büyük öneme sahip ifa uğruna edim hakkında çok sayıda tartışmalı sorun ortaya çıkmıştır. Ça-lışmamızda ifa uğruna edim konusu, bu temel sorunlar da analiz edilip benzer kurumlarla farklı yönleri ortaya konularak Türk Borçlar Kanunu, İsviçre Medeni Kanunu ve Alman Medeni Ka-nunu, doktrin ve mahkeme kararları da gözetilerek sistematik şekilde incelenmiştir.

In this doctoral thesis titled ‘Act for Purpose of Performance’, the debtor's attempt to fulfil the performance with a performance other than the performance owed and the legal con-sequences of this attempt are analysed. This attempt of the debtor for performance appears in different ways according to the purposes of the parties, and the legal consequences and the rights and obligations of the parties are shaped according to this characterisation. In our law, the rule is performance in accordance with the obligated performance, and the debtor is released from his obligation only by performing the performance agreed in the debt relationship, and the creditor can only demand the performance of this performance. However, it has become possib-le to fulfil the obligation with a performance different from the performance agreed in the debt relationship through legal possibilities, which are called performance substitutions and constitute an exception to this rule. Performance for the sake of performance, which constitutes the subject of our study, constitutes one of these exceptions, and provides the creditor with an additional opportunity to obtain its receivable, and the debtor with the opportunity to fulfil its obligation with an act different from the obligated act, thus gaining time for the realisation of the perfor-mance. Act for purpose of performance is not generally regulated by a statutory provision in Turkish and Swiss Law, and in German Law, it is adopted as a rule of interpretation in the se-cond paragraph of § 364 BGB, which regulates performance for the sake of performance. However, performance for the sake of performance is regulated under Art. 192 of the TCO, which regulates the performance of an existing obligation through the transfer of a receivable, and under Art. 556 of the TCO, which recognises as a legal presumption that the transfer made by the remitter to the remitter for the performance of the obligation in the underlying relationship is for the sake of performance. Many controversial problems have arisen about the performance for the sake of performance, which is not generally regulated in the laws, but is of great impor-tance especially in commercial life. In this study, the issue of performance for the sake of per-formance is analysed systematically by analysing these basic problems and revealing the diffe-rences with similar institutions, taking into account the Turkish Code of Obligations, Swiss Ci-vil Code and German Civil Code, doctrine and court decisions.
Act for purpose of performance
Keywords: as-signment of receivables for the sake of performance; Borçlar hukuku; edime uygun ifa kuralı; elements of act for purpose of performance; İfa ikameleri; ifa uğruna alacağın devri; ifa uğruna edimde tarafların hak ve borçları; ifa uğruna edimin hukuki nite-liği; ifa uğruna edimin unsurları; ifa uğruna havale; ifa yerine edim; legal nature of act for purpose of performance; Obligations (Law); performance in accordance with performance rule; performance in lieu of performance; remittance for the sake of performance; rights and obligati-ons of the parties in act for purpose of performance; Substitutes for performance; Turkey; Türkiye